Malignant Transformation of Ovarian Mature Teratoma: About a Case and Literature Review - Acharfi, Nisrine; Oualla, Karima; Ouahbi, Hajar; Benbrahim, Zineb; Arifi, Samia; Fatemi, Hind EL; Boubou, Meryem; Bouchikhi, Chahrazed; Banani, Abdelaziz; Mellas, Nawfel (International Journal of Innovative Research in Medical Science, 2019)
The cancerous teratoma of the ovary is a rare entity. We report the case of a 57-year-old woman post menauposal with malignant transformation of ovarian mature teratoma who was treated in the gynecology and medical oncology departments of CHU HASSAN II in Fez. The patient underwent bilateral adnexectomy and a total hysterectomy with omentectomy. The evolution was marked by the appearance of carcinomatosis nodules postoperatively. She received chemotherapy with platinum and taxanes .she had complete remission after 6 cycles and has remained under good control at present.